Cavity Pattern Formation and Its Dynamics of Fiber Fuse in Single-Mode Optical Fibers - Shuto, Yoshito (Journal of Informatics and Mathematical Sciences, 2020)
The nonlinear oscillation model using the Van der Pol equation was able to phenomenologically explain the formation of periodic cavities, the cavity shape, and the regularity of the cavity pattern in the core layer as a result of the relaxation oscillation and cavity compression and/or deformation. We assumed the relationships between the parameters of the population dynamics of interacting self-oscillators using the Kuramoto model and the fiber fuse propagation, and found an equation describing the power dependence of the periodic cavity interval. The experimentally determined cavity intervals at \(P_th ≤ P_0 ≤ 5\) W satisfied this equation. Furthermore, the experimental cavity intervals at \(P_0 >6\) W can be explained by considering the power dependence of the propagation velocity of the fiber fuse and the constant period of the Van der Pol oscillator.